Lumbar and pelvis movement comparison between cross-court and long-line topspin forehand in table tennis: based on musculoskeletal model - He, Yuqi; Liang, Minjun; Fang, Yufei; Fekete, Gusztáv; Baker, Julien S.; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Cross-court and the long-line topspin forehand is the common and basic stroke skill in table tennis. The purpose of this study was to investigate the differences in lumbar and pelvis movements between cross-court and long-line topspin forehand strokes in table tennis based on musculoskeletal demands using OpenSim. Materials and Methods: The eight-camera Vicon system and Kistler force platform were used to measure kinematics and kinetics in the lumbar and pelvis movement of sixteen participants (Weight: 69.89 ± 1.58 kg; Height: 1.73 ± 0.03 m; Age: 22.89 ± 2.03 years; BMI: 23.45 ± 0.69 kg/m2; Experience: 8.33 ± 0.71 years) during cross-court and long-line topspin forehand play. The data was imputed into OpenSim providing the establishment of the Giat2392 musculoskeletal model for simulation. One-dimensional statistical parametric mapping and independent samples t-test was performed in MATLAB and SPSS to analyze the kinematics and kinetics. Results: The results show that the range of motion, peak moment, and maximum angle of the lumbar and pelvis movement in cross-court play were significantly higher than in the long-line stroke play. The moment of long-line in the sagittal and frontal plane was significantly higher than cross-court play in the early stroke phase. Conclusion: The lumbar and pelvis embody greater weight transfer and greater energy production mechanisms when players performed cross-court compared to long-line topspin forehand. Beginners could enhance their motor control strategies in forehand topspin skills and master this skill more easily based on the results of this study.